(3GdJHjjf Ydi eKGd Gdjbjfs - (3efPQ Hf SYjO GdHdhWis ((3eMehO Hf CMeO Hf EHQGgje GdaGQSj s)
(3ChdgG (B:s
(3GdMeO ddg GdMejO GdeLjO GdeHOi GdPj CMSf cd TF Ndbg hHOC Ndb GdEfSGf ef Wjf Ke LYd fSdg ef SdGdI ef eGA egjf s
(3BNQgG (B:s
((3GdMeO ddg QH GdYGdejf(B) (3hjMeOhf QHge dCfge YdehG Cfg de jXdege hdcf XdehG CfaSge Je cJGH HMeOGddg hYhfg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3GdJUha hGdBOGH GdTQYjIs